Novel Probiotic Isolation of Coconut Water's Helpful Lactic Acid Bacteria Cure Covid-19 Patients - Suryani, Suryani; Purnawati , Yuliesi; Gemaeka Putri, Sindy; Rahmawati, Rahmawati; Akbar , Yustitia; Yusra , Yusra (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Probiotics from coconut water lactic acid bacteria have not isolated nor identified them, and no one has studied that these probiotics can help cure Covid-19 patients. This study aimed to isolate and identify probiotic lactic acid bacteria in coconut water, both morphologically, physiologically, and biochemically. Further studied his ability to help cure Covid-19 patients. Using coconut water samples, probiotics are isolated by isolating lactic acid bacteria through dilution methods and pour plate methods. The medium used is MRSA+ CaCO3 0.3%. Physiological and morphological identification. The following identification is to perform biochemical tests such as the Gram test. The results showed that there were 73 bacterial isolates and 24 fungal isolates, consisting of 4 species of bacteria, Pediococcus sp, Lactobacillus paracasei, and Lactobacillus plantarum, as well as candida sp and rhizopus fungi. In comparison, the results of the antimicrobial analysis showed that Lactobacillus plantarum has better antimicrobial ability against the pathogen bacteria Pseudomonas aureginosa. Lactobacillus plantarum's antimicrobial ability is less good against S. aureus bacteria. These findings suggest that probiotics from coconut water can be isolated and may aid the healing of Covid-19 patients. This study has implications that in the future Covid-19 patients can be helped with coconut water.